Edwin McMasters Stanton papers - Stanton, Edwin McMasters, 1814-1869.
Correspondence, letterbooks, reports, printed matter, memorabilia, maps, and other papers relating chiefly to Stanton's role as U.S. secretary of war under Abraham Lincoln and Andrew Johnson and to his role in the politics of Reconstruction. Other topics include the conduct of the Civil War, the radical wing of the Republican Party, Lincoln's assassination, and Stanton's evaluation of U.S. Army generals.
Correspondents include the Stanton family, George Bancroft, Henry Ward Beecher, James Buchanan, Benjamin F. Butler, Simon Cameron, Salmon P. Chase, Roscoe Conkling, Charles A. Dana, Thomas Ewing, William Pitt Fessenden, William Lloyd Garrison, Ulysses S. Grant, John Hay, Andrew Johnson, Reverdy Johnson, Francis Lieber, Abraham Lincoln, George Brinton McClellan, Winfield Scott, William Henry Seward, Philip Henry Sheridan, William T. Sherman, Thaddeus Stevens, Harriet Beecher Stowe, Charles Sumner, Benjamin Tappan, Lyman Trumbull, and Gideon Welles.
Microfilm edition available
Microfilm produced from originals in Manuscript Division.
Lawyer, U.S. attorney general, and U.S. secretary of war.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Bancroft, George, -- 1800-1891 -- Correspondence; Beecher, Henry Ward, -- 1813-1887 -- Correspondence; Buchanan, James, -- 1791-1868 -- Correspondence; Butler, Benjamin F. -- 1818-1893 -- Correspondence; Cameron, Simon, -- 1799-1889 -- Correspondence; Chase, Salmon P. -- 1808-1873 -- Correspondence; Conkling, Roscoe, -- 1829-1888 -- Correspondence; Dana, Charles A. -- 1819-1897 -- Correspondence; Ewing, Thomas, -- 1789-1871 -- Correspondence; Fessenden, William Pitt, -- 1806-1869 -- Correspondence; Garrison, William Lloyd, -- 1805-1879 -- Correspondence; Grant, Ulysses S. -- 1822-1885 -- Correspondence; Hay, John, -- 1838-1905 -- Correspondence; Johnson, Andrew, -- 1808-1875.; Johnson, Andrew, -- 1808-1875 -- Correspondence; Johnson, Reverdy, -- 1796-1876 -- Correspondence; Lieber, Francis, -- 1800-1872 -- Correspondence; Lincoln, Abraham, -- 1809-1865.; Lincoln, Abraham, -- 1809-1865 -- Assassination; Lincoln, Abraham, -- 1809-1865 -- Correspondence; McClellan, George Brinton, -- 1826-1885 -- Correspondence; Scott, Winfield, -- 1786-1866 -- Correspondence; Seward, William Henry, -- 1801-1872 -- Correspondence; Sheridan, Philip Henry, -- 1831-1888 -- Correspondence; Sherman, William T. -- 1820-1891 -- Correspondence; Stevens, Thaddeus, -- 1792-1868 -- Correspondence; Stowe, Harriet Beecher, -- 1811-1896 -- Correspondence; Sumner, Charles, -- 1811-1874 -- Correspondence; Tappan, Benjamin, -- 1773-1857 -- Correspondence; Trumbull, Lyman, -- 1813-1896 -- Correspondence; Welles, Gideon, -- 1802-1878 -- Correspondence; Stanton family -- Correspondence; United States. -- War Department; Republican Party (U.S. : 1854- ); Generals -- United States; Reconstruction (U.S. history, 1865-1877); United States -- Armed Forces -- Officers; United States -- History -- Civil War, 1861-1865.; United States -- Politics and government -- 1861-1865.; United States -- Politics and government -- 1865-1877.; Cabinet officers; Lawyers